Ds MJ Goddefroy en Christeliknasionale onderwys - Botha, Schalk Jacobus (Hervormde teologiese studies, 1987)
Rev MJ Goddefroy and Christian-National educationProfessor CH Rautenbach can be honoured as an excellent exponent of the principle of Christian-national education, based on the same views as the Nederduitsch Hervormde Church. In a tribute to him the purpose of this paper is to look into the matter of the Rev MJ Goddefroy and Christian-national education. Goddefroy came to South Africa exactly one hundred years ago in 1887 to become a minister in the Nederduitsch Hervormde Church and he on his part could be seen as one of the earlier exponents of the same principle.